Neural stem cells to cerebral cortex: Emerging mechanisms regulating progenitor behavior and productivity - Dwyer, Noelle; Chen, Bin; Chou, Shen; Hippenmeyer, Simon; Nguyen, Laurent; Ghashghaei, Troy (Journal of Neuroscience)
This review accompanies a 2016 SFN mini-symposium presenting examples of current studies that address a central question: How do neural stem cells (NSCs) divide in different ways to produce heterogeneous daughter types at the right time and in proper numbers to build a cerebral cortex with the appropriate size and structure? We will focus on four aspects of corticogenesis: cytokinesis events that follow apical mitoses of NSCs; coordinating abscission with delamination from the apical membrane; timing of neurogenesis and its indirect regulation through emergence of intermediate progenitors; and capacity of single NSCs to generate the correct number and laminar fate of cortical neurons. Defects in these mechanisms can cause microcephaly and other brain malformations, and understanding them is critical to designing diagnostic tools and preventive and corrective therapies.

Robust draws in balanced knockout tournaments - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Tkadlec, Josef
Balanced knockout tournaments are ubiquitous in sports competitions and are also used in decisionmaking and elections. The traditional computational question, that asks to compute a draw (optimal draw) that maximizes the winning probability for a distinguished player, has received a lot of attention. Previous works consider the problem where the pairwise winning probabilities are known precisely, while we study how robust is the winning probability with respect to small errors in the pairwise winning probabilities. First, we present several illuminating examples to establish: (a) there exist deterministic tournaments (where the pairwise winning probabilities are 0 or 1) where one optimal draw is much more robust than the other; and (b) in general, there exist tournaments with slightly suboptimal draws that are more robust than all the optimal draws. The above examples motivate the study of the computational problem of robust draws that guarantee a specified winning probability. Second, we present a polynomial-time algorithm for approximating the robustness of a draw for sufficiently small errors in pairwise winning probabilities, and obtain that the stated computational problem is NP-complete. We also show that two natural cases of deterministic tournaments where the optimal draw could be computed in polynomial time also admit polynomial-time algorithms to compute robust optimal draws.

Mating and longevity in ant males - Metzler, Sina; Heinze, Jürgen; Schrempf, Alexandra (Ecology and Evolution)
Across multicellular organisms, the costs of reproduction and self-maintenance result in a life history trade-off between fecundity and longevity. Queens of perennial social Hymenoptera are both highly fertile and long-lived, and thus, this fundamental trade-off is lacking. Whether social insect males similarly evade the fecundity/longevity trade-off remains largely unstudied. Wingless males of the ant genus Cardiocondyla stay in their natal colonies throughout their relatively long lives and mate with multiple female sexuals. Here, we show that Cardiocondyla obscurior males that were allowed to mate with large numbers of female sexuals had a shortened life span compared to males that mated at a low frequency or virgin males. Although frequent mating negatively affects longevity, males clearly benefit from a “live fast, die young strategy” by inseminating as many female sexuals as possible at a cost to their own survival.

Cytokinin response factors integrate auxin and cytokinin pathways for female reproductive organ development - Cucinotta, Mara; Manrique, Silvia; Guazzotti, Andrea; Quadrelli, Nadia; Mendes, Marta; Benková, Eva; Colombo, Lucia (Development)
The developmental programme of the pistil is under the control of both auxin and cytokinin. Crosstalk between these factors converges on regulation of the auxin carrier PIN-FORMED 1 (PIN1). Here, we show that in the triple transcription factor mutant cytokinin response factor 2 (crf2) crf3 crf6 both pistil length and ovule number were reduced. PIN1 expression was also lower in the triple mutant and the phenotypes could not be rescued by exogenous cytokinin application. pin1 complementation studies using genomic PIN1 constructs showed that the pistil phenotypes were only rescued when the PCRE1 domain, to which CRFs bind, was present. Without this domain, pin mutants resemble the crf2 crf3 crf6 triple mutant, indicating the pivotal role of CRFs in auxin-cytokinin crosstalk.

Modular architecture and unique teichoic acid recognition features of choline-binding protein L CbpL contributing to pneumococcal pathogenesis - Gutierrez-Fernandez, Javier; Saleh, Malek; Alcorlo, Martín; Gómez Mejóa, Alejandro; Pantoja Uceda, David; Treviño, Miguel; Vob, Franziska; Abdullah, Mohammed; Galán Bartual, Sergio; Seinen, Jolien; Sánchez Murcia, Pedro; Gago, Federico; et al. (Scientific Reports)
The human pathogen Streptococcus pneumoniae is decorated with a special class of surface-proteins known as choline-binding proteins (CBPs) attached to phosphorylcholine (PCho) moieties from cell-wall teichoic acids. By a combination of X-ray crystallography, NMR, molecular dynamics techniques and in vivo virulence and phagocytosis studies, we provide structural information of choline-binding protein L (CbpL) and demonstrate its impact on pneumococcal pathogenesis and immune evasion. CbpL is a very elongated three-module protein composed of (i) an Excalibur Ca 2+ -binding domain -reported in this work for the very first time-, (ii) an unprecedented anchorage module showing alternate disposition of canonical and non-canonical choline-binding sites that allows vine-like binding of fully-PCho-substituted teichoic acids (with two choline moieties per unit), and (iii) a Ltp-Lipoprotein domain. Our structural and infection assays indicate an important role of the whole multimodular protein allowing both to locate CbpL at specific places on the cell wall and to interact with host components in order to facilitate pneumococcal lung infection and transmigration from nasopharynx to the lungs and blood. CbpL implication in both resistance against killing by phagocytes and pneumococcal pathogenesis further postulate this surface-protein as relevant among the pathogenic arsenal of the pneumococcus.

Asymptotic analysis of noisy fitness maximization, applied to metabolism & growth - De Martino, Daniele; Masoero, Davide (Journal of Statistical Mechanics: Theory and Experiment)
We consider a population dynamics model coupling cell growth to a diffusion in the space of metabolic phenotypes as it can be obtained from realistic constraints-based modelling. In the asymptotic regime of slow diffusion, that coincides with the relevant experimental range, the resulting non-linear Fokker–Planck equation is solved for the steady state in the WKB approximation that maps it into the ground state of a quantum particle in an Airy potential plus a centrifugal term. We retrieve scaling laws for growth rate fluctuations and time response with respect to the distance from the maximum growth rate suggesting that suboptimal populations can have a faster response to perturbations.

Dissipative Few-Body Quantum Systems - Jochum, Clemens
Within the scope of this thesis, we show that a driven-dissipative system with few ultracold atoms can exhibit dissipatively bound states, even if the atom-atom interaction is purely repulsive. This bond arises due to the dipole-dipole inter- action, which is restricted to one of the lower electronic energy states, resulting in the distance-dependent coherent population trapping. The quality of this al- ready established method of dissipative binding is improved and the application is extended to higher dimensions and a larger number of atoms. Here, we simu- late two- and three-atom systems using an adapted approach to the Monte Carlo wave-function method and analyse the results. Finally, we examine the possi- bility of finding a setting allowing trimer states but prohibiting dimer states. In the context of open quantum systems, such a three-body bound states corre- sponds to the driven-dissipative analogue of a Borromean state. These states can be detected in modern experiments with dipolar and Rydberg-dressed ultracold atomic gases.

Commutativity in the algorithmic Lovasz local lemma - Kolmogorov, Vladimir (Proceedings - Annual IEEE Symposium on Foundations of Computer Science)
We consider the recent formulation of the Algorithmic Lovász Local Lemma [1], [2] for finding objects that avoid "bad features", or "flaws". It extends the Moser-Tardos resampling algorithm [3] to more general discrete spaces. At each step the method picks a flaw present in the current state and "resamples" it using a "resampling oracle" provided by the user. However, it is less flexible than the Moser-Tardos method since [1], [2] require a specific flaw selection rule, whereas [3] allows an arbitrary rule (and thus can potentially be implemented more efficiently). We formulate a new "commutativity" condition, and prove that it is sufficient for an arbitrary rule to work. It also enables an efficient parallelization under an additional assumption. We then show that existing resampling oracles for perfect matchings and permutations do satisfy this condition. Finally, we generalize the precondition in [2] (in the case of symmetric potential causality graphs). This unifies special cases that previously were treated separately.

Reconstruction of haplotype-blocks selected during experimental evolution. - Franssen, Susan; Barton, Nicholas H; Schlötterer, Christian (Molecular Biology and Evolution)
The genetic analysis of experimentally evolving populations typically relies on short reads from pooled individuals (Pool-Seq). While this method provides reliable allele frequency estimates, the underlying haplotype structure remains poorly characterized. With small population sizes and adaptive variants that start from low frequencies, the interpretation of selection signatures in most Evolve and Resequencing studies remains challenging. To facilitate the characterization of selection targets, we propose a new approach that reconstructs selected haplotypes from replicated time series, using Pool-Seq data. We identify selected haplotypes through the correlated frequencies of alleles carried by them. Computer simulations indicate that selected haplotype-blocks of several Mb can be reconstructed with high confidence and low error rates, even when allele frequencies change only by 20% across three replicates. Applying this method to real data from D. melanogaster populations adapting to a hot environment, we identify a selected haplotype-block of 6.93 Mb. We confirm the presence of this haplotype-block in evolved populations by experimental haplotyping, demonstrating the power and accuracy of our haplotype reconstruction from Pool-Seq data. We propose that the combination of allele frequency estimates with haplotype information will provide the key to understanding the dynamics of adaptive alleles.

Error-robust modes of the retinal population code - Prentice, Jason; Marre, Olivier; Ioffe, Mark; Loback, Adrianna; Tkacik, Gasper; Berry, Michael (PLoS Computational Biology)
Across the nervous system, certain population spiking patterns are observed far more frequently than others. A hypothesis about this structure is that these collective activity patterns function as population codewords–collective modes–carrying information distinct from that of any single cell. We investigate this phenomenon in recordings of ∼150 retinal ganglion cells, the retina’s output. We develop a novel statistical model that decomposes the population response into modes; it predicts the distribution of spiking activity in the ganglion cell population with high accuracy. We found that the modes represent localized features of the visual stimulus that are distinct from the features represented by single neurons. Modes form clusters of activity states that are readily discriminated from one another. When we repeated the same visual stimulus, we found that the same mode was robustly elicited. These results suggest that retinal ganglion cells’ collective signaling is endowed with a form of error-correcting code–a principle that may hold in brain areas beyond retina.

Only the combination of mathematics and agent based simulations can leverage the full potential of evolutionary modeling: Comment on “Evolutionary game theory using agent-based methods” by C. Adami, J. Schossau and A. Hintze - Hilbe, Christian; Traulsen, Arne (Physics of Life Reviews)

Formin’ a nuclear protection - Renkawitz, Jörg; Sixt, Michael K (Cell)
In this issue of Cell, Skau et al. show that the formin FMN2 organizes a perinuclear actin cytoskeleton that protects the nucleus and its genomic content of migrating cells squeezing through small spaces.

Immune priming in arthropods: an update focusing on the red flour beetle - Milutinovic, Barbara; Peuß, Robert; Ferro, Kevin; Kurtz, Joachim (Zoology)

Comparative genomic analysis of Haemophilus haemolyticus and nontypeable Haemophilus influenzae and a new testing scheme for their discrimination - Hu, Fang; Rishishwar, Lavanya; Sivadas, Ambily; Mitchell, Gabriel; King, Jordan; Murphy, Timothy; Gilsdorf, Janet; Mayer, Leonard; Wang, Xin (Journal of Clinical Microbiology)
Haemophilus haemolyticus has been recently discovered to have the potential to cause invasive disease. It is closely related to nontypeable Haemophilus influenzae (NT H. influenzae). NT H. influenzae and H. haemolyticus are often misidentified because none of the existing tests targeting the known phenotypes of H. haemolyticus are able to specifically identify H. haemolyticus. Through comparative genomic analysis of H. haemolyticus and NT H. influenzae, we identified genes unique to H. haemolyticus that can be used as targets for the identification of H. haemolyticus. A real-time PCR targeting purT (encoding phosphoribosylglycinamide formyltransferase 2 in the purine synthesis pathway) was developed and evaluated. The lower limit of detection was 40 genomes/PCR; the sensitivity and specificity in detecting H. haemolyticus were 98.9% and 97%, respectively. To improve the discrimination of H. haemolyticus and NT H. influenzae, a testing scheme combining two targets (H. haemolyticus purT and H. influenzae hpd, encoding protein D lipoprotein) was also evaluated and showed 96.7% sensitivity and 98.2% specificity for the identification of H. haemolyticus and 92.8% sensitivity and 100% specificity for the identification of H. influenzae, respectively. The dual-target testing scheme can be used for the diagnosis and surveillance of infection and disease caused by H. haemolyticus and NT H. influenzae.

Surprises in numerical expressions of physical constants - Amir, Ariel; Lemeshko, Mikhail; Tokieda, Tadashi (American Mathematical Monthly)
In science, as in life, "surprises" can be adequately appreciated only in the presence of a null model, what we expect a priori. In physics, theories sometimes express the values of dimensionless physical constants as combinations of mathematical constants like π or e. The inverse problem also arises, whereby the measured value of a physical constant admits a "surprisingly" simple approximation in terms of well-known mathematical constants. Can we estimate the probability for this to be a mere coincidence, rather than an inkling of some theory? We answer the question in the most naive form.

Safety assured formal model driven design of the multifunction vehicle bus controller - Jiang, Yu; Liu, Han; Song, Houbing; Kong, Hui; Gu, Ming; Sun, Jiaguang; Sha, Lui
In this paper, we present a formal model-driven engineering approach to establishing a safety-assured implementation of Multifunction vehicle bus controller (MVBC) based on the generic reference models and requirements described in the International Electrotechnical Commission (IEC) standard IEC-61375. First, the generic models described in IEC-61375 are translated into a network of timed automata, and some safety requirements tested in IEC-61375 are formalized as timed computation tree logic (TCTL) formulas. With the help of Uppaal, we check and debug whether the timed automata satisfy the formulas or not. Within this step, several logic inconsistencies in the original standard are detected and corrected. Then, we apply the tool Times to generate C code from the verified model, which was later synthesized into a real MVBC chip. Finally, the runtime verification tool RMOR is applied to verify some safety requirements at the implementation level. We set up a real platform with worldwide mostly used MVBC D113, and verify the correctness and the scalability of the synthesized MVBC chip more comprehensively. The errors in the standard has been confirmed and the resulted MVBC has been deployed in real train communication network.

Libration of strongly oriented polar molecules inside a superfluid - Redchenko, Elena; Lemeshko, Mikhail (ChemPhysChem)
We study a polar molecule immersed in a superfluid environment, such as a helium nanodroplet or a Bose–Einstein condensate, in the presence of a strong electrostatic field. We show that coupling of the molecular pendular motion, induced by the field, to the fluctuating bath leads to formation of pendulons—spherical harmonic librators dressed by a field of many-particle excitations. We study the behavior of the pendulon in a broad range of molecule–bath and molecule–field interaction strengths, and reveal that its spectrum features a series of instabilities which are absent in the field-free case of the angulon quasiparticle. Furthermore, we show that an external field allows to fine-tune the positions of these instabilities in the molecular rotational spectrum. This opens the door to detailed experimental studies of redistribution of orbital angular momentum in many-particle systems. © 2016 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim

Purification of ovine respiratory complex i results in a highly active and stable preparation - Letts, James A; Degliesposti, Gianluca; Fiedorczuk, Karol; Skehel, Mark; Sazanov, Leonid A (Journal of Biological Chemistry)
NADH-ubiquinone oxidoreductase (complex I) is the largest (∼1 MDa) and the least characterized complex of the mitochondrial electron transport chain. Because of the ease of sample availability, previous work has focused almost exclusively on bovine complex I. However, only medium resolution structural analyses of this complex have been reported. Working with other mammalian complex I homologues is a potential approach for overcoming these limitations. Due to the inherent difficulty of expressing large membrane protein complexes, screening of complex I homologues is limited to large mammals reared for human consumption. The high sequence identity among these available sources may preclude the benefits of screening. Here, we report the characterization of complex I purified from Ovis aries (ovine) heart mitochondria. All 44 unique subunits of the intact complex were identified by mass spectrometry. We identified differences in the subunit composition of subcomplexes of ovine complex I as compared with bovine, suggesting differential stability of inter-subunit interactions within the complex. Furthermore, the 42-kDa subunit, which is easily lost from the bovine enzyme, remains tightly bound to ovine complex I. Additionally, we developed a novel purification protocol for highly active and stable mitochondrial complex I using the branched-chain detergent lauryl maltose neopentyl glycol. Our data demonstrate that, although closely related, significant differences exist between the biochemical properties of complex I prepared from ovine and bovine mitochondria and that ovine complex I represents a suitable alternative target for further structural studies.

Real time analysis of the apical hook development - Zhu, Qiang; Žádníková, Petra; Smet, Dajo; Van Der Straeten, Dominique; Benková, Eva (Plant Hormones)
Mechanisms for cell protection are essential for survival of multicellular organisms. In plants, the apical hook, which is transiently formed in darkness when the germinating seedling penetrates towards the soil surface, plays such protective role and shields the vitally important shoot apical meristem and cotyledons from damage. The apical hook is formed by bending of the upper hypocotyl soon after germination, and it is maintained in a closed stage while the hypocotyl continues to penetrate through the soil and rapidly opens when exposed to light in proximity of the soil surface. To uncover the complex molecular network orchestrating this spatiotemporally tightly coordinated process, monitoring of the apical hook development in real time is indispensable. Here we describe an imaging platform that enables high-resolution kinetic analysis of this dynamic developmental process. © Springer Science+Business Media New York 2017.

Termination of shoot gravitropic responses by auxin feedback on PIN3 polarity - Rakusová, Hana; Abbas, Mohamad; Han, Huibin; Song, Siyuan; Robert, Hélène; Friml, Jirí (Current Biology)
Plants adjust their growth according to gravity. Gravitropism involves gravity perception, signal transduction, and asymmetric growth response, with organ bending as a consequence [1]. Asymmetric growth results from the asymmetric distribution of the plant-specific signaling molecule auxin [2] that is generated by lateral transport, mediated in the hypocotyl predominantly by the auxin transporter PIN-FORMED3 (PIN3) [3–5]. Gravity stimulation polarizes PIN3 to the bottom sides of endodermal cells, correlating with increased auxin accumulation in adjacent tissues at the lower side of the stimulated organ, where auxin induces cell elongation and, hence, organ bending. A curvature response allows the hypocotyl to resume straight growth at a defined angle [6], implying that at some point auxin symmetry is restored to prevent overbending. Here, we present initial insights into cellular and molecular mechanisms that lead to the termination of the tropic response. We identified an auxin feedback on PIN3 polarization as underlying mechanism that restores symmetry of the PIN3-dependent auxin flow. Thus, two mechanistically distinct PIN3 polarization events redirect auxin fluxes at different time points of the gravity response: first, gravity-mediated redirection of PIN3-mediated auxin flow toward the lower hypocotyl side, where auxin gradually accumulates and promotes growth, and later PIN3 polarization to the opposite cell side, depleting this auxin maximum to end the bending. Accordingly, genetic or pharmacological interference with the late PIN3 polarization prevents termination of the response and leads to hypocotyl overbending. This observation reveals a role of auxin feedback on PIN polarity in the termination of the tropic response. © 2016 Elsevier Ltd